MANAGING VIOLENCE AND AGGRESSION: GRADUATE-ENTRY NURSING STUDENTS' RESPONSES TO PRE-EMPTIVE COMMUNICATION SKILLS EDUCATION. - Moir, Chris; Baby, Maria (Kaitiaki Nursing Research, 2022)
Background: Violence and aggression toward nurses are workplace hazards that have been exacerbated by the COVID-19 pandemic. In clinical practice placements, nursing students sometimes bear the brunt of aggression from both patients and staff. The skills to respond safely and appropriately to these workplace hazards should be taught before students undertake clinical practice experiences. Therefore, teaching de-escalation skills early in the nursing programme is vital for student safety, and perhaps ultimately for their retention in the nursing workforce. Objectives: To determine the effectiveness of early communication skills training to enhance nursing students' aggression management skills while on clinical placement. Design: A quasi-experimental design using pre- and post-tests of communication competence following an education module delivered as part of the curriculum. Sample and setting: Participants were students in a master of nursing science pre-registration programme. Methods: Thackrey's Confidence in Coping with Patient Aggression Instrument and the Interpersonal Communication Competence Scale were administered at baseline before the communication session was taught. The same questionnaires were administered after the participants had completed clinical placements in acute care and mental health. Results: There were 33 nursing student participants. Outcome measures indicated a significant increase in both aspects of communication confidence and competence from baseline across the two placements for the combined cohorts. Conclusion: The study highlights the need to deliver communication skills training early in the nursing programme to enable nursing students to develop confidence in dealing with aggression across all areas of health care.